Cluster-Fault Control Strategies for Modular Multilevel Converters - Oliver Kalmbach; Christoph M. Hackl (IEEE Open Journal of the Industrial Electronics Society)
Modular multilevel converters (MMCs) are widely used for high-voltage and high-power applications. They are highly scalable, modular, and flexible in operation. However, this comes with the price of a large number of components, such as semiconductors and capacitors. Each of those components is prone to failure. This article presents four fault-tolerant control strategies for MMCs under severe failures: cluster faults that have been rarely discussed in literature for MMCs. Three fault modes are discussed and four cluster-fault control strategies are proposed. All approaches are derived in detail and validated by simulation and measurement results, including transitions from healthy to faulty operation for different power factors and power steps. The results show that proper functionality of the MMC by the proposed cluster-fault control strategies is still achievable even under the resulting voltage constraints. The proposed cluster-fault control strategies are simple to implement and allow for 1) an easy integration into (existing) systems and 2) an improved fault tolerance of MMCs.